A HAART‐Breaking Review of Alternative Antiretroviral Administration: Practical Considerations with Crushing and Enteral Tube Scenarios. Issue 11 (20th October 2016) - Huesgen, Emily; DeSear, Kathryn E.; Egelund, Eric F.; Smith, Renata; Max, Blake; Janelle, Jennifer
Abstract : Selection of an appropriate antiretroviral regimen for the patient infected with human immunodeficiency virus can be challenging, as various considerations must be taken into account including viral resistance mutations, patient comorbidities, drug interactions, and the potential for drug‐related adverse effects and toxicities. Treatment is further complicated when a clinical scenario arises requiring an alteration in the dosage form. Factors ranging from dysphagia to administration through an enteral feeding tube can affect decisions regarding antiretroviral dosage forms. Limited pharmacokinetic data exist regarding the alteration of antiretroviral medications from their original form. Bioavailability may vary substantially between dosage forms, which can lead to unpredictable drug concentrations. Supratherapeutic or subtherapeutic antiretroviral drug concentrations can result in increased toxicity, virologic failure, or the emergence of drug resistance. We performed a systematic literature search to review the available antiretroviral literature on the modification of solid dosage forms as well as alternative routes of administration of oral antiretroviral agents and their application to clinical practice.